Human brain activity during exposure to radiofrequency fields emitted by cellular phones - Hietanen, Maila; Kovala, T; Hämäläinen, A-M (Scandinavian Journal of Work, Environment & Health, 2000)
' ' OBJECTIVES ': 'The aim of this study was to explore the possible influence of radiofrequency (RF) radiation exposure on human brain function. ' ' METHODS ': 'The electroencephalographic (EEG) activity of 19 volunteers was quantitatively analyzed. Ten of the subjects were men (28-48 years of age) and 9 were women (32-57 years of age). The sources of exposure were 5 different cellular phones (analogue and digital models) operating at a frequency of 900 MHz or 1800 MHz. The EEG activity was recorded in an awake, closed-eyes situation. Six 30-minute experiments, including 1 sham exposure, were made for each subject. The duration of a real exposure phase was 20 minutes. ' ' RESULTS ': 'Exposure to one of the phones caused a statistically significant change in the absolute power at the delta band of the EEG recording. However, no difference was seen in the relative power of the same band, and no changes occurred during exposure to other phones at any frequency bands. ' ' CONCLUSION ': 'The findings of this study suggest that exposure to radiofrequency fields emitted by cellular phones has no abnormal effects on human EEG activity. The observed difference in 1 parameter was probably caused by statistical chance.
Keywords: electroencephalogram; electromagnetic fields; exposure; mobile phone; nonionizing radiation